Класифікації і види прогалин у цивільному законодавстві - Завальнюк, Сергій Володимирович; Завальнюк, С. В.; Zavalniuk, Serhii (ВД "Гельветика", 2020)
У статті визначено класифікації і види прогалин у цивільному законодавстві України. Запропоновано та обґрунтовано виділення окремих класифікацій та видів прогалин у цивільному законодавстві. Також у праці досліджено правову природу, причини виникнення різних видів прогалин у цивільному законодавстві, їхній вплив на динаміку перебігу цивільних правовідносин.

A relevant and practically significant issue remains the classification of gaps in civil legislation. As noted by A.N. Kalashnik, highlighting certain types of gaps with the aim of understanding them more deeply, finding out the reasons for their appearance, and then overcoming or eliminating them, will improve the legislative process, improve the rulemaking technique of legislative acts, and ensure legality in the implementation of norms. From the point of view of improving legal regulation, it is important to solve the problem of classification of gaps in the legislation and their criteria, since depending on whether the gaps belong to a particular class (type), the question, methods and methods of overcoming them by law enforcement entities are solved differently, in particular public authorities. The research of the legal nature of classifications of types of gaps in civil legislation was investigated one way or another in their works: Akimov V.I., Alekseev S.S., Viliyansky S.I., Zabigailo V.K., Ioffe O.S., Kalashnik V. M., Kaplya A., Klim, S.I., Kutafin O.E., Lazarev V.V., Mikhailovsky I.V., Polyanik K., Ryabova D.N., Skakun O.F., Tarnopolskaya, A.N., Tikhomirov Yu.A., Todyka Yu.N., Yavorsky V.D., Uransky F.R., Yavich L.S. and many others. However, the vast majority of these authors, exploring the issue of classifications of types of gaps, almost always identify the concept of gaps in law and gaps in legislation. Also, most of these authors almost did not consider the civil law aspect of the question, which makes this article even more relevant. The article defines the classifications and types of gaps in the civil legislation of Ukraine. The author proposes and substantiates the allocation of individual classifications and types of gaps in civil law. Also, the work explores the legal nature, the causes of various types of gaps in civil law, their impact on the dynamics of the course of civil relations.
Завальнюк С. В. Класифікації і види прогалин у цивільному законодавстві / С. В. Завальнюк // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 11-17.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; акт цивільного законодавства; законодавство; прогалини в цивільному законодавстві; цивільне законодавство; уявні прогалини; реальні прогалини; повні прогалини; неповні прогалини; первинні прогалини; вторинні прогалини; формальні прогалини; матеріальні прогалини; законодавчі прогалини; технічні прогалини; нормативний вакуум в акті цивільного законодавства; неповнота нормативно-правового акту цивільного законодавства; колізійні прогалини; кваліфікований дефект; civil law act; legislation; gaps in civil legislation; civil legislation; imaginary gaps; real gaps; full gaps; incomplete gaps; primary gaps; secondary gaps; formal gaps; material gaps; legislative gaps; technical gaps; regulatory vacuum in act of civil law; conflict gaps; qualified defect